2011
DOI: 10.1016/j.bone.2011.05.013
|View full text |Cite
|
Sign up to set email alerts
|

MicroCT morphometry analysis of mouse cancellous bone: Intra- and inter-system reproducibility

Abstract: The agreement between measurements and the relative performance reproducibility among different microcomputed tomography (microCT) systems, especially at voxel sizes close to the limit of the instruments, is not known. To compare this reproducibility 3D morphometric analyses of mouse cancellous bone from distal femoral epiphyses were performed using three different ex vivo microCT systems: GE eXplore Locus SP, Scanco μCT35 and Skyscan 1172. Scans were completed in triplicate at 12μm and 8μm voxel sizes and mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 37 publications
2
33
1
Order By: Relevance
“…45 Second, the growth plate comprises a clear structure that is easy to recognize and define. Third, there have previously been a relatively large number of studies that have provided results for murine femurs, and values for the accuracy and reproducibility of these measures have been assessed, 32,49,50 which ensured the comparability and reproducibility of our experiments. Radiological analyses and histological staining demonstrated that aged male mice and OVX female mice exhibited a decreased BMD, a lower BV/TV, fewer and thinner trabeculae, and increased trabecular spacing, which indicates that the models of aged osteoporosis and OVX osteoporosis were successfully established.…”
Section: Discussionmentioning
confidence: 99%
“…45 Second, the growth plate comprises a clear structure that is easy to recognize and define. Third, there have previously been a relatively large number of studies that have provided results for murine femurs, and values for the accuracy and reproducibility of these measures have been assessed, 32,49,50 which ensured the comparability and reproducibility of our experiments. Radiological analyses and histological staining demonstrated that aged male mice and OVX female mice exhibited a decreased BMD, a lower BV/TV, fewer and thinner trabeculae, and increased trabecular spacing, which indicates that the models of aged osteoporosis and OVX osteoporosis were successfully established.…”
Section: Discussionmentioning
confidence: 99%
“…The right femur without scaffold was similarly examined to serve as control. Micro-CT was performed using a Skyscan 1076 instrument (Skyscan) [32]. Each femur was scanned for 260 slices each above and below the midpoint of the scaffold for a total of 8.2 mm in length.…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, a study should report a minimal set of image acquisition parameters (voxel size, X-ray tube potential, and integration times); a minimal description of trabecular bone (bone volume fraction, trabecular number, trabecular thickness, and trabecular separation); and a minimal description of cortical bone (total cross-sectional area, cortical bone area, cortical area fraction, and average cortical thickness). Reporting these parameters is essential, as different µCT machines do not give comparable results [43]. It is easy to see why the use of µCT is becoming commonplace in evaluating CSD models, and this modality will continue to evolve.…”
Section: Csd Outcome Measuresmentioning
confidence: 99%